2019
DOI: 10.3343/alm.2019.39.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Autoantibodies Against Nucleoporin p62 in Sera of Patients With Primary Biliary Cholangitis

Abstract: Background Primary biliary cholangitis (PBC) is an autoimmune liver disease characterized by specific autoantibodies. We evaluated the prevalence of autoantibodies against nucleoporin p62 (anti-p62) in PBC patients' sera to determine whether it can be a marker for PBC, in comparison with other immunological and biochemical parameters. We validated the performance of our in-house ELISA technique. Methods Serum samples were collected from 135 PBC patients. Thirty patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…The ANA pattern in PBC includes multiple nuclear dots (MND-ANA) and nuclear membrane-associated ANAs (NM-ANAs). About 30% of patients manifest anti-nuclear envelope (NE) positivity [ 13 , 14 , 15 , 16 ]. In the majority of cases, anti-NM antibodies target gp210 and p62 proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The ANA pattern in PBC includes multiple nuclear dots (MND-ANA) and nuclear membrane-associated ANAs (NM-ANAs). About 30% of patients manifest anti-nuclear envelope (NE) positivity [ 13 , 14 , 15 , 16 ]. In the majority of cases, anti-NM antibodies target gp210 and p62 proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that s-p62-Abs are positive not only for cancers such as HCC, colorectal cancer, and breast cancer but also for conditions characterized by chronic inflammation and fibrosis, such as primary biliary cholangitis ( 2 , 5 , 26 , 27 ). Even in our study, the positivity rate of s-p62-Abs was not significantly higher in patients with HCC than in those with LC and CH.…”
Section: Discussionmentioning
confidence: 99%
“…Optical density (OD) was measured with an automatic plate reader (Multiscan RC, Labsystem, Vantaa, Finland). Detection of anti-p62 antibodies was performed according to the procedure described by Bauer and Habior [17].…”
Section: Autoantibodies Assaymentioning
confidence: 99%